2005
DOI: 10.1111/j.1945-5100.2005.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of the Sudbury impact structure, Canada: Impact-induced versus orogenic deformation-A review

Abstract: Abstract-Orogenic deformation, both preceding and following the impact event at Sudbury, strongly hinders a straightforward assessment of impact-induced geological processes that generated the Sudbury impact structure. Central to understanding these processes is the state of strain of the Sudbury Igneous Complex, the solidified impact melt sheet, its underlying target rocks, overlying impact breccias and post-impact sedimentary rocks. This review addresses (1) major structural, metamorphic and magmatic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 70 publications
1
57
1
Order By: Relevance
“…The elliptical shape in plan view (Fig. 1), the dip of lower contacts at surface (Rousell 1984) and the asymmetric deep structure (Milkereit et al 1992) of the layered SIC is a function of its post-impact orogenic deformation (Shanks and Schwerdtner 1991;Cowan and Schwerdtner 1994;Riller et al 1998;Riller 2005). Along with the overlying Onaping Formation, a heterolithic impact melt breccia (Muir and Peredery 1984;Stöffler et al 1994), and post-impact sedimentary rocks, the synformal Main Mass of the SIC forms the Sudbury Basin (Brocoum and Dalziel 1974).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The elliptical shape in plan view (Fig. 1), the dip of lower contacts at surface (Rousell 1984) and the asymmetric deep structure (Milkereit et al 1992) of the layered SIC is a function of its post-impact orogenic deformation (Shanks and Schwerdtner 1991;Cowan and Schwerdtner 1994;Riller et al 1998;Riller 2005). Along with the overlying Onaping Formation, a heterolithic impact melt breccia (Muir and Peredery 1984;Stöffler et al 1994), and post-impact sedimentary rocks, the synformal Main Mass of the SIC forms the Sudbury Basin (Brocoum and Dalziel 1974).…”
Section: Geological Settingmentioning
confidence: 99%
“…In contrast to short-term ("catastrophic") modes of dike formation, it has been suggested that emplacement of quartzdioritic melts on time scales on the order of tens to hundreds of thousands of years resulted from crater floor fracturing driven by isostatic readjustment of the crust (Wichmann and Schultz 1993), post-impact cooling and contraction of host target rocks below the Main Mass of the SIC (Riller 2005) and tectonism following crater formation (Therriault et al 2002). These modes of dike formation most likely involved laminar melt flow, during incremental opening of fractures in the crater floor.…”
Section: Introductionmentioning
confidence: 99%
“…Exterior to these gneisses are granite-greenstones of a lower metamorphic grade [Riller, 2005;Grieve et al, 2007]. The Vredefort dome is ~80 km in diameter, and comprises a 40 km diameter Archean core of deep crustal rocks, surrounded by an annular collar of mid-crustal rocks [Gibson et al, 1998;Lana et al, 2003].…”
Section: Grieve and Pilkingtonmentioning
confidence: 99%
“…The Vredefort dome is ~80 km wide, and comprises a 40 km diameter Archean core of deep crustal rocks surrounded by an annular collar of mid-crustal rocks [Gibson et al, 1998;Lana et al, 2003]. At Sudbury there is also a decrease in metamorphic grade with distance from the Sudbury Igneous Complex (SIC) [Riller, 2005;Grieve et al, 2008]. The erosion level at Vredefort is postulated to be around 5-10 km [McCarthy et al, 1990;Gibson and Reimold, 2001], and a few kilometers outside the SIC at Sudbury [Dressler, 1984].…”
mentioning
confidence: 99%
“…Apart from the best-known and well-stud ied cases that used a va ri ety of meth ods, their or i gin is not yet fully clear (Saul, 1978;Taud and Par rot, 1992;Brink et al, 1997;Tur tle and Pierazzo, 1998;Riller, 2005;Juhlin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%